ANALISA FRAMING PEMBERITAAN KEBIJAKAN PEMERINTAH DALAM PENANGANAN COVID-19 DI MEDIA ONLINE - OKTAFIANI HERLINA (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2021)
The coronavirus has caused social, economic, and phsychological effects all over the world. Thisvirus is easy to spread and can pose a risk of death. Indonesia is one of the countries most affected bythis virus. At the beginning of its appearance, the information about those overflowed in the massmedia. The media inform about Covid-19 and government policies in handling the virus. This textbased qualitative research was conducted by framing analysis. Robert Entmant's framing scheme isused to describe the reality of reporting on government policies related to handling of Covid-19 inonline media. The data collection techniques is through observation, documentation, and literaturestudy. The research process is carried out by interpreting the stage of defining the problem,estimating problems, making moral decisions and emphasizing the solution. As a result, the newsframing of the handling of Covid-19 was built in line with the policies conveyed by the government inthe mass media. Public communication carried out by the government can determine the direction ofthe news narrative in the media. The policies taken by the government always have a political,economic, and health narrative. These three things become a narrative that can not be separated inthe news. The media often criticize government policies which are often inappropriate anduncoordinated so they are fed up with those informations sooner. The media should be able to givehope to the public to be optimistic and enthusiastic in dealing with the pandemic situation. Keywords: Covid-19, Coronavirus, Media, Framing